The Unique Features of Typhoon Rai (2021): An Observational Study - Petilla, Clint Eldrick R (Archīum Ateneo, 2025)
Tropical Cyclone (TC) RAI (2021) made a devastating landfall in the Siargao-Dinagat Islands of the southeastern Philippines on December 16, 2021, causing about USD 942 M in damage, 405 reported deaths and 52 missing. Yet, observational studies on the environmental conditions during TC RAI remain limited, and a comparison with other landfalling TCs were not done. To shed light on the factors that made this TC reach a maximum sustained wind speed (MSW) of 105 kts (194.5 kph) and 915 hPa mean sea level pressure according to the WMO-IBTrACS, this study investigated the meteorological statistics of this TC relative to other landfalling TCs in the Philippines from 1979 to 2020 and the environmental features with cases having similar landfalling month, location, and track. When compared with Philippine landfalling TCs from 1979 to 2020, this TC, among violent typhoons, ranked second in terms of MSW and translational speed. Moreover, the TC had a westward movement, faster translational speed, larger radius, and greater intensity when compared to seven other TCs that made landfall in the same month and region. The environmental factors along the path of TC RAI that may have contributed to its intensification include, but are not limited to, the above normal SST (+ 0.5 to 1.5 °C) and ocean heat content, high low-level relative humidity (RH), and high specific humidity. These factors resulted in strong low-level convergence and intensification until landfall. Composite analysis of and comparison with the other seven landfalling TCs reveal that the atmospheric conditions during TC RAI had a consistently higher near-surface RH850hPa–500 hPa, which may have helped sustain its movement across the central Philippines. Moisture from the Philippine Sea was also drawn into the central Philippines, which received at least 125–150 mm of rainfall. The extension of the western North Pacific Subtropical High along 20 °N and strong easterly flow may have facilitated the TC’s straight and westward movement. The findings of this study are essential for quantitatively ranking the destructiveness of this event, while identifying key indicators of TC intensification and trajectory for landfalling TCs in central and southern Philippines.